Dichloroacetate improves immune dysfunction caused by tumor‐secreted lactic acid and increases antitumor immunoreactivity. Issue 5 (16th March 2013) - Ohashi, Toshimitsu; Akazawa, Takashi; Aoki, Mitsuhiro; Kuze, Bunya; Mizuta, Keisuke; Ito, Yatsuji; Inoue, Norimitsu
<x xml:space="preserve">Abstract</x> The activation of oncogenic signaling pathways induces the reprogramming of glucose metabolism in tumor cells and increases lactic acid secretion into the tumor microenvironment. This is a well‐known characteristic of tumor cells, termed the Warburg effect, and is a candidate target for antitumor therapy. Previous reports show that lactic acid secreted by tumor cells is a proinflammatory mediator that activates the IL‐23/IL‐17 pathway, thereby inducing inflammation, angiogenesis and tissue remodeling. Here, we show that lactic acid, or more specifically the acidification it causes, increases arginase I (ARG1) expression in macrophages to inhibit T‐cell proliferation and activation. Accordingly, we hypothesized that counteraction of the immune effects by lactic acid might suppress tumor development. We show that dichloroacetate (DCA), an inhibitor of pyruvate dehydrogenase kinases, targets macrophages to suppress activation of the IL‐23/IL‐17 pathway and the expression of ARG1 by lactic acid. Furthermore, lactic acid‐pretreated macrophages inhibited CD8+ T‐cell proliferation, but CD8+ T‐cell proliferation was restored when macrophages were pretreated with lactic acid and DCA. DCA treatment decreased ARG1 expression in tumor‐infiltrating immune cells and increased the number of IFN‐γ‐producing CD8+ T cells and NK cells in tumor‐bearing mouse spleen. Although DCA treatment alone did not suppress tumor growth, it increased antitumor immunotherapeutic activity of Poly(IC) in both CD8+ T cell‐ and NK cell‐sensitive tumor models. Therefore, DCA acts not only on tumor cells to suppress glycolysis but also on immune cells to improve the immune status modulated by lactic acid and to increase the effectiveness of antitumor immunotherapy.